Sosialisasi dan Pelatihan Pengelolaan Air Bersih di Pondok Pesantren Binaul Ummah Kuningan - Akhmaddhian, Suwari; Rifai, Iman Jalaludin; Supartono, Toto; Agustian, Agung Gumelar; Hermansyah, Dadan; Royvaldo, Royvaldo (Empowerment, 2023)
Water is one of the most important and useful substances for the survival of almost all living things on earth. Water is a material that covers about 71% of the earth's surface. Water is a very important primary need for humans and living creatures. More than 70% of the human body consists of water (75% in the brain, 75% in the heart, 86% in the lungs, 86% in the liver, 83% in the kidneys, 75% in the muscles, and 83% in the blood). Water is needed by all body organs in order to function perfectly, for example: in the process of eliminating toxins, lubricating the joints, helping the digestive process, stabilizing body temperature, and facilitating the body's metabolic processes. The method for carrying out service activities at this socialization stage is through lecture and discussion methods for activity participants, namely employees and students of the Binaul Ummah Kuningan Islamic Boarding School. The results of the activity are based on the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning Implementing Regulations of Government Regulation Number 66 of 2014 concerning Environmental Health. Water Standards for Hygiene and Sanitation Purposes is water used for individual and/or household hygiene purposes. Water sanitation includes monitoring, protecting and improving water quality. Conclusion Water resource management must meet health standards Air adalah salah satu zat paling penting dan berguna untuk kelangsungan hampir seluruh makhluk hidup di bumi. Air merupakan materi yang menutupi sekitar 71% dari permukaan di bumi. Air merupakan kebutuhan utama yang sangat penting bagi manusia dan makhluk hidup. Lebih dari 70% tubuh manusia terdiri dari air (75% di otak, 75% di jantung, 86% di paru-paru, 86% di hati 83% di ginjal, 75% di otot, dan 83% di darah). Air diperlukan oleh semua organ tubuh agar dapat berfungsi dengan sempurna, misal: dalam proses pembuangan racun (toxic), pelicin bagi sendi-sendi, membantu proses pencernaan, menstabilkan suhu tubuh, dan memperlancar proses metabolisme tubuh. Metode pelaksanaan kegiatan pengabdian tahap sosialisasi ini yaitu dengan metode ceramah dan diskusi peserta kegiatan yaitu  karyawan dan santri Pondok Pesantren Binaul Ummah Kuningan. Hasil kegiatan yaitu Berdasarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 2 Tahun 2023 tentang Peraturan Pelaksanaan Peraturan Pemerintah Nomor 66 Tahun 2014 Tentang Kesehatan Lingkungan  Standar Air untuk Keperluan Higiene dan Sanitasi adalah air yang digunakan untuk keperluan higiene perorangan dan/atau rumah tangga. Penyehatan air meliputi pengawasan, pelindungan, dan peningkatan kualitas air. Simpulan pengelolaan sumberdaya air harus memenuhi standar kesehatan